Psychosocial Pair. Demands and Challenges from the Perspective of the Professionals Involved in the Schools of the Ñuble Region - Cárcamo-Vásquez, Héctor (2020)
The object of study that is addressed in this article corresponds to specific challenges and demands that professionals that make up the psychosocial pairs of several schools in the Ñuble Region identify. Due to the nature of the object, the approach corresponds to the qualitative methodology based on the socio-phenomenological approach. The data production was made in 10 working groups constituted by professionals that make up psychosocial pairs. As main findings we see that, from the perspective of the actors, the task of the psychosocial pairs is mediated by three fundamental critical issues, which operate from totality: context, normativity and action. Thus, psychosocial pairs work in schools as a result of a pro-inclusion policies framework, which has been pressing for more than a decade. Its incorporation to the educational system presents various difficulties linked to job insecurity, diffuse roles and functions, as well as instability and discontinuity of psychosocial intervention processes with children and their respective families. In sum, there is a pedagogical disciplinary closure that hinders the integration of the psychosocial pair as a validated unit for school improvement.